Aplikasi Tindakan ROM pada Lansia di Panti Werdha : Systematic Literature Review - Zela, Nurma; Aglusi Badri, Isna (Pustaka Galeri Mandiri, 2025)
Older adults residing in nursing homes are at high risk of joint contractures, functional decline, and decreased quality of life due to limited mobility. Range of motion (ROM) exercises have been identified as a key intervention to mitigate these challenges. This systematic literature review aims to synthesize recent empirical evidence on the application of ROM exercises for institutionalized older adults, highlighting their effectiveness, barriers to implementation, and recommendations for future practice. Following PRISMA guidelines, a structured search was conducted in Scopus for publications from 2022 to 2024. Inclusion criteria targeted peer-reviewed studies addressing ROM interventions in nursing homes or long-term care settings. After screening and full-text assessment, 10 studies met the eligibility criteria and were included for synthesis. The review found that structured ROM programs improve joint flexibility, enhance functional capacity, reduce the risk of pressure ulcers, and promote mental well-being among nursing home residents. Active ROM demonstrated superior benefits compared to passive ROM interventions. However, barriers such as limited staffing resources, lack of caregiver training, and resident motivation challenges were noted. Facility-based ROM interventions under structured supervision were generally more effective than home-based programs. ROM exercises represent a practical, low-risk, and evidence-supported strategy to preserve mobility and functional independence among institutionalized older adults. Future research should explore culturally adapted, technology-assisted, and sustainable ROM interventions with long-term follow-up to maximize benefits in diverse geriatric populations